ANALISIS FAKTOR YANG MEMPENGARUHI PERUBAHAN TATA CARA ADAT PERKAWINAN SUKU MINANGKABAU DI KELURAHAN DURI TIMUR KECAMATAN MANDAU KABUPATEN BENGKALIS PROVINSI RIAU - Tria Pertiwi; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims ats describe the changes in the implementation of the procedures of customary marriage the Minangkabau and to know the factors that affect the change in the implementation of the procedures of customary marriage the Minangkabau in Duri Timur Mandau district Bengkalis Regency Riau Province. The Population in this study is the tribal society Minangkabau located in the village of Duri Timur of the amount of 1.250 families with samples of 125 families. The instrument collection of data and questionnaire consisting of 40 question and interview. Then the data analysis techniques to analyze data that are descriptive analysis of the sort of descriptive set of quantitative. Based on the calculation the percentage answers of respondents obtained an answer, at 87% and not as big as 13% of the aspects of the changes in the way traditional marriage rates Minangkabau in Duri Timur Mandau district Bengkalis Regency Riau Province. Besides, that is undergoing a change is an activity marisiak, maminang, batuka tando, ask permission-mahanta siriah, the night bainai, the reception at the child’s daro, manjapuik marapulai, manjalang-mahanta siriah, mamulangkan tando, balantuang kaniang, mangaruak nasi kuniang, bamain coki and babako-babaki. Regarding the factors that affect change in the implementation of the procedures of customary marriage rates Minangkabau in Duri Timur Mandau district Bengkalis Regency Riau Province is the answer, by 43% and not as big as the 57%. The factors affect change in the way traditional marriage rates Minangkabau that is, there is contact with other cultures, the desire to move forward, tolerance of deeds in a way that is not an offense-the violation o law, public dissatisfactionon the fields of life, values that people should always strive to improve his life and attitude had new things and so on.Key Words: Change The Way Traditional Marriage Rates Minangkabau